Efectividad antiemética del ondansetrón comparado con el dimenhidrinato en dos momentos de administración en colecistectomias bajo anestesia inhalatoria - Salizar Moquillaza, Nieves Amalia (2011)
To determine the timing of administration of more effective antiemetic ondansetron compared with dimenhydrinate in cholecystectomy under inhalational general anesthesia. Material and methods: Prospective cohorts study design 4 groups of 50 patient’s which of them to receive antiemetic drugs: ondansetrón and dimenhydrinate in different moments: at anesthetic induction or at the end of surgery. We use chi X2 test, F test and variance analysis to determine the affectivity of ondansetrónvs. dimenhydrinate and the better time to administration. Results: The frequency of presentation of nausea and vomiting is less in the group that receive ondansetrón at the end of the surgery with statistic significance (p<0.05). The middle time of the begin nauseas and vomiting was more in the group that receive ondansetrón at the end of surgery without statistics significance (p>0.05). The number of episodes of nauseas and vomiting by patient was less en the group that receive ondansetrón at the end ofsurgery with statistic significance (p<0.05). The needless to rescue antiemetic’s was less in the group that receive ondansetrón at the induction and dimenhydrinate at the end of surgery with statistics significance (p<0.05). Conclusions: Ondansetrón was more effective than dimenhydrinate. The time to administration of the drugs at the end of surgery offer more affectivity than at the induction anesthetic